2003
DOI: 10.1590/s1516-35982003000100012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of four cattle breeds using microsatellite markers

Abstract: -Four cattle breeds (Gyr, Nellore, Guzerat and Holstein) were analyzed by amplification of genomic DNA using microsatellite loci to evaluate the genetic diversity within and among them. DNA samples of 18 animals from each breed were collected to access the genetic content of them. Allele frequencies were calculated and used to generate a Nei's genetic distance matrix what was used to build a dendrogram following UPGMA clustering. As expected, Holstein breed was the most distinct from the other breeds: 1.15 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 8 publications
6
23
1
7
Order By: Relevance
“…Machado et al (2003b) found that in a 5/8 Charolais 3/8 Zebu crossbred population heterozygosity was between 0.468 and 0.755 (average 0.646) for the four markers used in their research. In our study heterozygosity was between 0.578 and 1.0 (average 0.865) (Table 3), this value being higher than the average heterozygosity obtained with nine microsatellites for the Gyr (0.305) and Holstein (0.339) populations by Machado et al (2003a). In a study to incorporate more markers in the bovine genetic linkage map, Bishop et al (1994) found an average heterozygosity of 0.747 in Bos taurus X Bos indicus F 1 crosses.…”
Section: Resultscontrasting
confidence: 58%
“…Machado et al (2003b) found that in a 5/8 Charolais 3/8 Zebu crossbred population heterozygosity was between 0.468 and 0.755 (average 0.646) for the four markers used in their research. In our study heterozygosity was between 0.578 and 1.0 (average 0.865) (Table 3), this value being higher than the average heterozygosity obtained with nine microsatellites for the Gyr (0.305) and Holstein (0.339) populations by Machado et al (2003a). In a study to incorporate more markers in the bovine genetic linkage map, Bishop et al (1994) found an average heterozygosity of 0.747 in Bos taurus X Bos indicus F 1 crosses.…”
Section: Resultscontrasting
confidence: 58%
“…These differences could be caused by the different origin of the breeds. A relevant distance between Holstein and another cattle breed was observed by Machado et al (2003). A similar genetic distance between Limousin and Charolais breeds (0.138) was observed by Maudet et al (2002).…”
Section: Blood Groups Microsatellitesupporting
confidence: 61%
“…The general heterozygosity was lower in the Chinese native population (0.69-0.76) (Zhou et al, 2005). The heterozygosity value observed in the Slovak Holstein population (0.707) was higher than that reported for North American Holsteins (0.61) by Vallejo et al (2003) and for the Holstein population (0.513) by Machado et al (2003).…”
Section: Resultsmentioning
confidence: 52%
“…This result does not vary much with the results of Kumari et al (2014) against 9 nations of sheep in India who obtain the A allele frequency (+) higher than the frequency of allele (-). According to Machado et al (2003), if the Ho value is lower than the He value, it indicates a degree of endogamy (mating within the group). Furthermore, Javanmard et al (2005) found that heterozygosity with a value below 50% indicates the low variation of a gene in the population.…”
Section: Allele Frequencies Heterozygosity and Pic (Polymorphic Contmentioning
confidence: 99%